2010
DOI: 10.1002/jnr.22392
|View full text |Cite
|
Sign up to set email alerts
|

Synapse loss in dementias

Abstract: Synaptic transmission is essential for nervous system function, and its dysfunction is a known major contributing factor to Alzheimer’s-type dementia. Antigen-specific immunochemical methods are able to characterize synapse loss in dementia through the quantification of various synaptic proteins involved in the synaptic cycle. These immunochemical methods applied to the study of Alzheimer’s disease (AD) brain specimens have correlated synaptic loss with particularly toxic forms of amyloid-β protein and have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 58 publications
4
123
1
1
Order By: Relevance
“…Expression of the IBMPFD mutants reduces the number of dendritic spines in cultured hippocampal neurons by 10%-18%. Since synapse loss has been suggested in various neurological disorders associated with dementia (61)(62)(63)(64)(65)(66)(67), the ability of VCP in the regulation of spinogenesis may be relevant to clinical features of dementia in patients. VCP does not represent the only example where a gene responsible for FTD is involved in neuronal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the IBMPFD mutants reduces the number of dendritic spines in cultured hippocampal neurons by 10%-18%. Since synapse loss has been suggested in various neurological disorders associated with dementia (61)(62)(63)(64)(65)(66)(67), the ability of VCP in the regulation of spinogenesis may be relevant to clinical features of dementia in patients. VCP does not represent the only example where a gene responsible for FTD is involved in neuronal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxidative stress and inflammatory cytokines have important roles in brain impairment and dementia progression (8). In addition, experimental evidence has indicated that synapse loss occurs in AD and VaD patients and studies revealed a strong correlation between synapse reduction and the severity of dementia (9). Although an increasing number of mechanistic pathological studies focused on VaD and hypoperfusion, no effective pharmacological intervention has been approved by the Food and Drug Administration (Silver Spring, MD, USA) and used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed therapeutic mechanism of Souvenaid™ on synaptic function makes it a clinically interesting drug in bv-FTD, that is, a neurodegenerative condition linked with different neuropathological substrata, all presenting synaptic dysfunction as a final common pathway [1,6,7,8]. Here, we thus decided to assess the effects of Souvenaid™ on these key symtomatological domains of bv-FTD, namely executive functions, behavioral symptomatology and social cognition [9].…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic dysfunction and loss is one of the final common pathways of neurodegeneration [1], thus potentially representing a relevant therapeutic target in different neurological conditions. Despite the possible clinical usefulness of targeting synaptic dysfunction, the currently available pharmacological options to reach this aim in the clinical setting are limited.…”
Section: Introductionmentioning
confidence: 99%